Effect of customized mineral supplement on blood biochemical profile, antioxidant indices and immunity in kids - YENGKHOM, ROJITA; VERMA, A K; DUTTA, NARAYAN; JADHAV, S E; PATTANAIK, A K (The Indian Journal of Animal Sciences, 2020)
The study was carried out to examine the effects of customized mineral supplement on blood-biochemical profile, antioxidant indices and immunity in kids. Kids (18) were randomly divided into 3 groups with 6 kids in each group in a CRD. The kids were randomly allocated into CON, CMM and CMS groups. In CON group, kids were offered a concentrate mixture without mineral mixture; however, kids in CMM and CMS groups were provided concentrate mixture having commercial and customized mineral supplement, respectively. The feeding trial lasted for 135 days. Haematocrit and serum glucose levels were significantly lower in CON as compared to CMS and CMM groups. The mean Hb was significantly higher in CMS relative to CON. Total protein was significantly higher in CMS group as compared to CMM and CON, while serum urea, albumin, globulin, A:G, serum enzymes (ALT and AST) did not differ significantly among treatments. The LPO levels were decreased in CMS group than CON. The CAT and GSH levels were comparable irrespective of treatments, however, SOD levels increased significantly in CMS followed by CMM and CON groups, respectively. The CMI response was significantly higher in CMS than CON and CMM groups. The mean antibody titer (log base2) against chicken RBC was significantly higher in CMS and CMM groups relative to CON. It may be concluded that the supplementation of customized mineral supplement considerably improved the haematological parameters, antioxidant indices and immune response in kids.